Institutional Arrangement in the Investment Sector through Inter-Organizational Communication - M. Widaningsih Widaningsih; Novianita Rulandari (Yayasan Ilomata, 2022)
Investment is one of the economic drivers in various countries, because investment will be able to have a very significant impact on economic development. Therefore, this investment growth has special attention in various regions to support the smooth development of investment. Therefore, investment services, especially in licensing development, have changed dynamically in line with global economic developments. This situation requires innovation in investment and licensing processes to improve the investment climate. Handling efforts can be carried out in various ways such as human resource development or organizational management aimed at facilitating services for the business community. Based on the newest phenomena and facts supported by data, the problems were analyzed using qualitative method approaches and descriptive analysis methods. Thus, a descriptive analysis method is applied to find facts by accurately interpreting and describing the group and individual characteristics of the phenomena found from the results of this study. The results of this research showed that the bureaucratic path in completing licensing was very long and had an impact on the increasingly expensive licensing fees, so that this will not support the objectives of investment policies in the region. It can be concluded that the problem lies in the institutional aspect of the agency that handles licensing and investment issues that exist in each region which are still weak in formal and informal regulations and their enforcement, so that the implementation of policies on investment is still very difficult to be implemented, or bad implementation. The implementated of law enforcement both formal and informal, one of them is supported by the synergy between policy actors and harmonization of communication among organizations because this will have an impact on making licensing easily for investment to cut long bureaucratic paths as well as expensive costs